A complex degradation signal in Cyclin A required for G(1) arrest, and a C-terminal region for mitosis. - Jacobs, H.W.; Keidel, E.; Lehner, C.F. (The EMBO Journal, 2001)
The destruction box (D-box) consensus sequence has been defined as a motif mediating polyubiquitylation and proteolysis of B-type cyclins during mitosis. We show here that the regions with similarity to D-boxes are not required for mitotic degradation of Drosophila Cyclin A. Instead of a simple D-box, a complex N-terminal degradation signal is present in this cyclin. Mutations that impair or abolish mitotic Cyclin A destruction delay progression through metaphase, but only when overexpressed. Moreover, these mutations prevent epidermal cells from entering the first G1 phase of embryogenesis and lead to a complete extra division cycle instead of a timely cell proliferation arrest. Residual Cyclin A activity after mitosis, therefore, has S phase-promoting activity. In principle, an S phase defect could also explain why epidermal cells fail to enter mitosis 16 in mutants lacking zygotic Cyclin A function. However, we demonstrate that this failure of mitosis is not caused simply by DNA replication or damage checkpoints. Entry into mitosis requires a function of Cyclin A that does not depend on the presence of the N-terminal region.